The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
Quality Control in Laboratory 2018
DOI: 10.5772/intechopen.73052
|View full text |Cite
|
Sign up to set email alerts
|

Quality Management Systems for Laboratories and External Quality Assurance Programs

Abstract: A quality management system (QMS) plans, controls, and improves the elements that impact on the achievement of the desired results by the laboratory and on the satisfaction of the users. There are different standards that establish requirements for the implementation of a quality management system for laboratories, and a cross comparison between them is shown. Additionally, external quality assurance or assessment (EQA) programs offer multiple benefits to laboratories: method validation, comparing of results w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 23 publications
(32 reference statements)
0
8
0
Order By: Relevance
“…The self-awareness of healthcare workers and the strengthening of biosafety training, aimed at risk assessments and quality control, will affect the reduction of the level of exposure to potential hazards ( 21 ). In this way, they influence the development of awareness of personal responsibility for the level of exposure within the laboratory ( 22 ). The study by Hailu HA et al concluded that by good organization of work through the subjects’ basic knowledge of accreditation, standard operating procedures, we can influence the subjects’ awareness and reduce the level of exposure to dangers in laboratories ( 23 ).…”
Section: Discussionmentioning
confidence: 99%
“…The self-awareness of healthcare workers and the strengthening of biosafety training, aimed at risk assessments and quality control, will affect the reduction of the level of exposure to potential hazards ( 21 ). In this way, they influence the development of awareness of personal responsibility for the level of exposure within the laboratory ( 22 ). The study by Hailu HA et al concluded that by good organization of work through the subjects’ basic knowledge of accreditation, standard operating procedures, we can influence the subjects’ awareness and reduce the level of exposure to dangers in laboratories ( 23 ).…”
Section: Discussionmentioning
confidence: 99%
“… 39 When the results from many methods are comparable to those from patient samples containing the same number of analytes, the EQA sample is considered commutable. 37 , 44 , 45 Nevertheless, cost-effectively attaining commutability poses a challenge for EQA providers when developing fit-for-purpose EQA materials. 12 The need for large sample volumes, a wide range of concentrations of the measurand, and sample stability has led providers to use materials treated with stabilizers and supplemented with materials of human or nonhuman origins, leading to EQA samples that are not commutable with authentic clinical samples.…”
Section: Eqa Sample Managementmentioning
confidence: 99%
“…Using the same procedure and assuming matrix-related bias, peer groups or participant groups are used to evaluate and classify laboratories because it is not feasible to compare them to the same given value. 44 , 47 , 48…”
Section: Eqa Sample Managementmentioning
confidence: 99%
“…A variety of quality standards can be implemented by laboratories, being requirements from ISO 9001 for the quality management system (QMS) the most widely used [26]. Briefly, ISO 9001 is characterized by a process-based approach following the plan-do-check-act cycle, not only focused on the quality of a product or service or the satisfaction of its users but on the way to obtain them.…”
Section: Quality Management Systemmentioning
confidence: 99%